Targeted expression of the arsenate reductase HAC1 identifies cell type specificity of arsenic metabolism and transport in plant roots. (10th October 2020) - Fischer, Sina; Sánchez-Bermejo, Eduardo; Xu, Xuejie; Flis, Paulina; Ramakrishna, Priya; Guerinot, Mary Lou; Zhao, Fang-Jie; Salt, David E
Abstract: High Arsenic Concentration 1 (HAC1), an Arabidopsis thaliana arsenate reductase, plays a key role in arsenate [As(V)] tolerance. Through conversion of As(V) to arsenite [As(III)], HAC1 enables As(III) export from roots, and restricts translocation of As(V) to shoots. To probe the ability of different root tissues to detoxify As(III) produced by HAC1, we generated A. thaliana lines expressing HAC1 in different cell types. We investigated the As(V) tolerance phenotypes: root growth, As(III) efflux, As translocation, and As chemical speciation. We showed that HAC1 can function in the outer tissues of the root (epidermis, cortex, and endodermis) to confer As(V) tolerance, As(III) efflux, and limit As accumulation in shoots. HAC1 is less effective in the stele at conferring As(V) tolerance phenotypes. The exception is HAC1 activity in the protoxylem, which we found to be sufficient to restrict As translocation, but not to confer As(V) tolerance. In conclusion, we describe cell type-specific functions of HAC1 that spatially separate the control of As(V) tolerance and As translocation. Further, we identify a key function of protoxylem cells in As(V) translocation, consistent with the model where endodermal passage cells, above protoxylem pericycle cells, form a 'funnel' loading nutrients and potentially toxic elements into the vasculature. Abstract : In roots we uncover cell type-specific functions of the arsenate reductase HAC1 spatially separating control of arsenic tolerance and translocation, and highlight the protoxylem in export of arsenic to shoots.